Implementasi Model PBL (Problem Based Learning) Untuk Meningkatkan Hasil Belajar Siswa di SMPN 5 Batukliang - Muhammad Yusril Yusup; Vera Wati (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Problem Based Learning Model emphasize student to improve student problem solving skills so that student’ learning achievement can enchance. The objective of this research was to improve student’ learning achievement through problem based learning model. The method which was applied in this research is eksperiment research. It. The results were obtained several findings, namely: student’ mastery was 63,16% in class control and 85% in class eksperiment. Based on the results of this eksperient can be concluded that implementation of problem based learning model was good to improve student’s learning achievement.